Efektivitas E-Learning Berbasis LMS Google Classroom Dengan Strategi Discovery Learning Materi Fluida Statis SMA - Ratnawati, Hemi; Sulisworo, Dwi (Universitas Halu Oleo, 2021)
This study aims to determine the effectiveness of Google Classroom with the static fluid material Discovery strategy. The research subjects were 31 students of class XII MIPA 1 SMA N 4 Yogyakarta. The method used is pre-experimental quantitative research using one group pretest-posttest design supported by quantitative data from the results of student response questionnaires. Google Classroom LMS with the Discovery strategy has a significant and effective effect, it is shown that the posttest student scores are greater than the pretest scores. The results obtained from the questionnaire on the aspects of language structure at intervals > 3.64- 3.9 criteria agree, the presentation aspect in the interval range> 3.51 - 4.03 criteria agree, and language structure in the interval range > 3.67 -3, 93 criteria agree. From the questionnaire, it was explained that the facilities for working with Google Classroom were easy and helped students during the online learning period. These results indicate that learning with the Google Classroom LMS with the Discovery strategy can effectively be used on static fluid.